2006
DOI: 10.1364/oe.14.006502
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-based polarization-sensitive Fourier domain optical coherence tomography using B-scan-oriented polarization modulation method

Abstract: Fiber-based high-speed polarization-sensitive Fourier domain optical coherence tomography (PS-FD-OCT) is developed at 840 nm wavelength using polarization modulation method. The incident state of polarization is modulated along B-scan. The spectrometer has a polarizing beamsplitter and two line-CCD cameras operated at a line rate of 27.7 kHz. From the 0th and 1st orders of the spatial frequencies along the B-scanning, a depth-resolved Jones matrix can be derived. Since continuous polarization modulation along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 54 publications
1
73
0
Order By: Relevance
“…19,20 PS-OCT can simultaneously provide phase-retardation tomography (P-OCT) and standard scattering OCT (S-OCT) images. This new type of OCT has been used for the investigation of the posterior [21][22][23][24][25] and anterior eye segments, 26 quantitative assessment of a retinal nerve fiber layer, [27][28][29][30] and follow-up investigations after glaucoma surgery. 31 Although it is known that PS-OCT has the potential to clearly visualize the trabecular meshwork, there are no evidence-based studies for proving this improved visibility.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 PS-OCT can simultaneously provide phase-retardation tomography (P-OCT) and standard scattering OCT (S-OCT) images. This new type of OCT has been used for the investigation of the posterior [21][22][23][24][25] and anterior eye segments, 26 quantitative assessment of a retinal nerve fiber layer, [27][28][29][30] and follow-up investigations after glaucoma surgery. 31 Although it is known that PS-OCT has the potential to clearly visualize the trabecular meshwork, there are no evidence-based studies for proving this improved visibility.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an optically clear hemoglobin-based blood substitute has also been used to displace blood and enable OCT imaging with minimal patient discomfort (Villard et al, 2002). Further, several Fourier domain PS-OCT techniques (Park et al, 2005;Yamanari et al, 2006;Zhang et al, 2004) have been reported recently and have received considerable attention due to the high data acquisition rates (e.g., acquisition at 80 to 110 fps), which can eliminate motion artifacts and reduce ischemia during blood-free optical imaging. This allows for comprehensive scanning of long arterial segments during a short balloon occlusion or even 1 bolus liquid flush without occlusion.…”
Section: Principle Of Polarization-sensitive Optical Coherence Tomogrmentioning
confidence: 99%
“…Polarization-sensitive OCT (PS-OCT) [22][23][24] analyzes the effect of tissue on the light polarization to provide a contrast mechanism other than light intensity. Different implementation of PS-OCT has been proposed for SD-OCT structure in the past years [25][26][27][28]. Optical coherence elastography (OCE) is another application of OCT imaging, which aims to study the mechanical properties of the tissue.…”
Section: Introductionmentioning
confidence: 99%